2021
DOI: 10.3389/fonc.2021.792347
|View full text |Cite
|
Sign up to set email alerts
|

Nomograms Combining Ultrasonic Features With Clinical and Pathological Features for Estimation of Delphian Lymph Node Metastasis Risk in Papillary Thyroid Carcinoma

Abstract: BackgroundThis work explores the clinical significance of Delphian lymph nodes (DLN) in thyroid papillary carcinoma (PTC). At the same time, a nomogram is constructed based on clinical, pathological, and ultrasonic (US) features to evaluate the possibility of DLN metastasis (DLNM) in PTC patients. This is the first study to predict DLNM using US characteristics.MethodsA total of 485 patients, surgically diagnosed with PTC between February 2017 and June 2021, all of whom underwent thyroidectomy, were included i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 26 publications
1
11
1
Order By: Relevance
“…Fifteen articles were excluded because they were repeated publication/overlapped samples ( n = 4), no surgical approach ( n = 3), outcomes different to those considered in the study ( n = 2), the nomograms were not reported ( n = 2), statistical model used to determine risk factors differed from logistic regression or Cox regression ( n = 2), nomograms used to evaluate the diagnostic accuracy of diffusion-weighted imaging ( n = 1), and a study related to micro PTC ( n = 1). Finally, 18 studies, for a total of 20 models, were included ( 10 , 19 , 20 , 29 , 35 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ). The studies included a total of 90,969 patients ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Fifteen articles were excluded because they were repeated publication/overlapped samples ( n = 4), no surgical approach ( n = 3), outcomes different to those considered in the study ( n = 2), the nomograms were not reported ( n = 2), statistical model used to determine risk factors differed from logistic regression or Cox regression ( n = 2), nomograms used to evaluate the diagnostic accuracy of diffusion-weighted imaging ( n = 1), and a study related to micro PTC ( n = 1). Finally, 18 studies, for a total of 20 models, were included ( 10 , 19 , 20 , 29 , 35 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ). The studies included a total of 90,969 patients ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…More than 50,000 patients were enrolled in the training set, 44,138 were used for validation of whom 3412 were in the external validation. Seventeen of the 19 studies were conducted in China ( 10 , 19 , 20 , 29 , 35 , 48 , 49 , 50 , 51 , 52 , 53 , 55 , 56 , 57 , 58 , 60 , 61 ), except for Kim's study, which was conducted in South Korea ( 54 ). Two studies began in 1997 and were completed in 2011 ( 49 ) and 2016 ( 54 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, nomograms play important roles in personalized risk stratification and help doctors in choosing the treatments when no guidelines exist, especially in the field of cancer ( 20 ). Previous studies ( 21 24 ) have demonstrated that nomograms have been useful in predicting CLNM risk in PTC patients, but there were relatively few reports for predicting CLNM risk in MTC patients. In our present study, a noninvasive nomogram model for the preoperative prediction of CLNM of MTC was built using US features.…”
Section: Discussionmentioning
confidence: 99%